New chronology for Ksâr ‘Akil (Lebanon) supports Levantine route of modern human dispersal into Europe - Bosch, Marjolein D. (Proc Natl Acad Sci U S A, 2015)
Modern human dispersal into Europe is thought to have occurred with the start of the Upper Paleolithic around 50,000–40,000 y ago. The Levantine corridor hypothesis suggests that modern humans from Africa spread into Europe via the Levant. Ksâr ‘Akil (Lebanon), with its deeply stratified Initial (IUP) and Early (EUP) Upper Paleolithic sequence containing modern human remains, has played an important part in the debate. The latest chronology for the site, based on AMS radiocarbon dates of shell ornaments, suggests that the appearance of the Levantine IUP is later than the start of the first Upper Paleolithic in Europe, thus questioning the Levantine corridor hypothesis. Here we report a series of AMS radiocarbon dates on the marine gastropod Phorcus turbinatus associated with modern human remains and IUP and EUP stone tools from Ksâr ‘Akil. Our results, supported by an evaluation of individual sample integrity, place the EUP layer containing the skeleton known as “Egbert” between 43,200 and 42,900 cal B.P. and the IUP-associated modern human maxilla known as “Ethelruda” before ∼45,900 cal B.P. This chronology is in line with those of other Levantine IUP and EUP sites and demonstrates that the presence of modern humans associated with Upper Paleolithic toolkits in the Levant predates all modern human fossils from Europe. The age of the IUP-associated Ethelruda fossil is significant for the spread of modern humans carrying the IUP into Europe and suggests a rapid initial colonization of Europe by our species.